(untitled) - Gussenhoven, Carlos (Cambridge, 2004)
Using examples from a wide variety of languages, this book reveals why speakers vary their pitch, what these variations mean, and how they are integrated into our grammars. All languages use modulations in pitch to form utterances. Pitch modulation encodes lexical "tone" to signal boundaries between morphemes or words, and encodes "intonation" to give words and sentences an additional meaning that isn't part of their original sense
Keywords: Tone (phonetics),Intonation (phonetics),Giọng điệu (ngữ âm),Ngữ điệu (ngữ âm)